Use of palm mid-fraction in dark chocolate as base filling centre at different storage temperatures - Selamat, Jinap; Ali, Abdelrahim Abdelbagi; Che Man, Yaakob; Yusoff, Mohd Suria Affandi (Taylor & Francis, 2000)
Dark chocolates filled with palm mid-fraction (PMF) were stored at different temperatures to evaluate the physical and chemical changes. Storage at low temperature (18°C) reduces the PMF migration to negligible extent. Higher storage temperatures (30 and 35°C) increased the PMF migration from the filling centre into the chocolate coating. As a consequence of fat migration, fatty acid composition, triglyceride composition, hardness, solid fat content, melting point and polymorphic structure changed, leading to bloom formation, which started by fat migration and was influenced by recrystallization tendency within the chocolate coating.